Change in Visual Function in Uveitis Patients after Treatment: An Experience from Nepal. (4th July 2018) - Sunam Gamal, Nita; Kharel (Sitaula), Ranju; Shah, Dev Narayan
ABSTRACT: Purpose : To assess the change in visual function in uveitis patients after treatment. Materials and methods : This one and a half year prospective study was conducted among 180 new uveitis patients. A questionnaire was used to assess the visual function in uveitis cases and analysis of effect size change was also done. Results : The male to female ratio was 1.3:1. The mean vision at presentation was 0.49 logMAR units, which improved to 0.39 logMAR units and 0.35 logMAR units by the 1st and 4th week but deteriorated to 0.62 logMAR units at the 6th week. Anterior uveitis and posterior uveitis patients had significant improvement ( p ≤0.001) in all three scales but panuveitis and intermediate uveitis had significant improvement ( p <0.05) in two scales. The effect size showed small to large change in all three scales. Conclusions : Visual function is adversely affected by uveitis, which can be improved after treatment.